Application of ecodrainage system in reducing the potential for flooding in the District of Sampang - Andikha, Fauzan; Yuniarto, Adhi (Sustinere: Journal of Environment and Sustainability, 2017)
Kamoning River watershed is one of the watersheds in Sampang. Sampang City experienced flooding almost every year caused by the overflow of the River Kamoning. One of the causes of flooding in that city is the high rainfall and a lack of rainwater catchment areas in the upper and middle Kamoning River watershed. To overcome these problems, it is necessary to use a system of flood discharge reduction eco drainage in the upstream and in the middle of Kamoning River watershed. This study used two scenarios of eco-drainage system: first is to change the land use in combination with the creation of retention ponds, the second scenario is to change the land use in combination with the creation of infiltration wells. From the analysis of large unknown, designed-flood discharge of 50 year-return period of Kamoning River basin is 289.361 m3/ sec. By using the first scenario, the designed-flood discharge can be reduced by 199.59 m3/s or 31.02%, while large designed-flood discharge can be reduced by 205.20 m3/s or 29.08% using second scenario. Efforts to reduce the discharge flood in Sampang can be effectively conducted by using the scenario 1.